0447 Racial disparities in patient outcomes and treatment engagement in cognitive behavioral therapy for insomnia among pregnant women. (25th May 2022) - Kalmbach, David; Cheng, Philip; Pitts, D'Angela; O'Brien, Louise; Seymour, Grace; Cuamatzi-Castelan, Andrea; Bazan, Luisa; Drake, Christopher
Abstract: Introduction: Insomnia affects over half of pregnant women, and epidemiological data suggest that insomnia rates are twice as high among black women relative to white women in pregnancy. Recently, cognitive behavioral therapy for insomnia (CBTI) has been supported as an efficacious intervention for prenatal insomnia. However, it remains unclear whether CBTI is equally efficacious across racial groups, which is necessary to help reduce race-related disparities in prenatal insomnia. Methods: This study is a secondary analysis of a single-site trial. Thirty-nine women who self-identified as white (n=24) and black (n=15) completed CBTI during pregnancy. Insomnia was measured using the Insomnia Severity Index (ISI). Before CBTI, patients reported sociodemographics. Treatment outcomes were collected a week after completing treatment during pregnancy. Results: Although racial groups did not differ in ISI before treatment, white patients reported significantly larger decreases in ISI relative to black patients after CBTI (-5.75 vs -2.13, p=.046). Notably, black women were less engaged in treatment than white women based on mean number of sessions attended (4.20 vs 5.54 sessions, p=.013). Even so, multivariate linear regression showed that posttreatment ISI was 4 points higher for black women than white women (b=4.10, p=.049) when controlling for baseline ISI (p=.001), obesity (p=.072), poverty (p=.091), sessions attended (p=.155), and short sleep (p=.406). Notably, 41.7% of white CBTI patients remitted relative to 26.7% of black CBTI patients, suggesting that white women are 56% more likely to remit from CBTI than black women. Conclusion: Our data suggest that black pregnant women exhibit poorer response to digital CBTI than white pregnant women. Moreover, racial disparities in CBTI response during pregnancy were not attributable to differences in session attendance. We must identify barriers to treatment response in black women, thereby guiding refinement to CBTI to provide better care for black women during pregnancy. Support (If Any): Ameriican Academy of Sleep Medicine